Eksistensi Lembaga Swadaya Masyarakat dalam Peningkatan Kapasitas Pemerintah Desa - Cahya Pratiwi, Lisa; Widhianto, Agung (Journal Governance and Politics (JGP), 2025)
This study analyzes the roles of NGO called Pandjer School in capacity development of local governments in Kebumen Regency. The research was conducted using qualitative methods through literature study and in-depth interviews. This research uses Jim Ife’s role theory (2013) which highlights the importance of community development and their active participation in the local development process. The results found that Pandjer School’s roles in improving the capacity of local governments in Kebumen is considered as optimal, despite the range of village facilitations achieved is still limited. This study brings several implications, such as deepen the understanding of the indicators that affect the effectiveness of NGOs in supporting local government capacity development and support the collaboration between NGO Pandjer School and local governments in Kebumen in improving community welfare at the local level. This study concludes that external factors such as local political and social conditions in Kebumen have an effect on the effectiveness of NGO Pandjer School in supporting local government capacity development, but this study has its limitations to fully capture this variability. Keywords: Non Governmental Organization, Village Government Capacity, Community Empowerment